BANKERS’ DEVIANT BEHAVIOUR AND JOB DEMANDS: ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT - C. Echezona-Anigbogu, Jovita; A. Okonkwo, Ejike; Obodo, Paul; Nwagbo, Ifeoma (African Journal of Social and Behavioural Sciences, 2024)
On the basis of the assumption of job demands-resources theory suggesting a link between perceived organizational support, job demands, and bankers’ deviant behaviour. This correlational study investigated the moderating role of perceived organizational support in job demands and bankers’ deviant behavior in a sample of commercial banks in Enugu metropolis, Enugu State, Nigeria. Three hundred and three bankers (303) comprising 119 males and 184 females between the ages of 23 and 52 years (M=43.13, SD=4.36) participated in the study. They were selected via a two-stage (cluster and purposive) sampling technique. The 16- item job demands scale, 19-item bankers’ deviance scale, and 17-item perceived organizational support scale were completed by the participants. Hayes regression-based process macro version 3.0 for SPSS showed that the workload dimension of job demands was negatively associated with minor bankers’ deviant behaviour. The qualitative and conflict dimensions of job demands are positively associated with major bankers’ deviant behaviour. Perceived organizational support is positively associated with minor bankers’ deviant behaviour. Perceived organisational support moderated the relationship between the qualitative dimension of job demands and minor bankers’ deviant behaviour. Perceived organisational support moderated the relationship between the qualitative dimension of job demands and major bankers’ deviant behaviour. In light of these findings, policymakers in the Nigerian banking industry should create conditions to increase the support given to commercial bankers with the purpose of reducing qualitative and conflicting job demands to minimize counterproductive work behaviour, such as major bankers’ deviant behaviour.